Value and Character Education Based on Qurâ€™anic - Nurhaeny, Eva (International Conference of Moslem Society, 2016)
This essay discusses based on Qurâ€™anic value and character education. In gobalization era, it has great impact on young behaviour change such as fighting, free sex, drug and other delinquencies. The occurred result is serious enough and it cannot be assumed just as a simple matter again, mainly that the subjects and the victim are young people whose have professions as students. The fact indicates that education world has to give an important role toward preventing national moral decadency in the effort of preparing the better future young generation. In this regard, we are aware that the education goal, basically, is to build better morality of human being or in another term is to â€œhumanize the human beingâ€. An idea regarding the significance of character education was appeared as a given solution in answering the morality problem in Indonesian education world. Character education is part of value education. That why, looking for the character education concept has been very urgent in the effort of preparing excellent, faithful, professional and personalized leaner as being asked by the education goal. The essence of characterized behavior actually is the psychological totality form which includes the whole human individual potency of cognitive, affective and psycho-motoric aspects, and also socio-cultural totality function in the context of interaction with God, him or herself, other human beings and the environment in his or her long life. Furthermore, in Qurâ€™anâ€™s teaching, the figure of the Messenger Peace be upon him (PBUH) is viewed as â€œthe model human beingâ€. In this context, the concept of Qurâ€™anic charactereducation can be found through three moral dimensions that should be actualized in human being personality. They are the morality toward Allah (spiritual quotient/ intelligence), the morality toward our self (emotional quotient) and the morality toward Allahâ€™s creatures, human being and environment (social quotient). Then, school should make the Holy Qurâ€™an as the foundation of character educationâ€™s implementation whereas the implementation form in the school can be developed through intra-curricular, extra-curricular or personality and school culture development.